Excellent piezoelectric and electrical properties of lithium-doped ZnO nanowires for nanogenerator applications - Chang, Yu-Tsui; Chen, Jul-Yuan; Yang, Tzu-Ping; Huang, Chun-Wei; Chiu, Chung-Hua; Yeh, Ping-Hung; Wu, Wen-Wei (My University, 2014)
The well-aligned Li-doped zinc oxide nanowires (ZnO NWs) were successfully grown on Si substrates with seed layer by the hydrothermal method. The presence of Li in ZnO NWs is confirmed through EELS spectrum analysis. The acceptor energy level of the Li dopant is estimated to be 93.6 meV from the temperature-dependent PL spectra. From the SQUID measurements, the coercivity and saturation magnetization of the Li-doped ZnO NWs at room temperature are found to be 166 Oe and 9.64 memu/g, respectively. Additionally, the Li-doped ZnO NWFET confirms that the NWs were p-type with a high carrier mobility of 14.59 cm(2/)V s and an effective hole carrier concentration of 1.13 x 10(17) CM-3. The piezoelectric response of the Li-doped ZnO NWs produces much higher piezoelectric output current, voltage, and power than pure ZnO NWs. These results indicated that p-type ZnO NWs are a promising candidate for nanogenerator devices. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: ZnO; Lithium-doped; Piezoelectric property; Hydrothermal method; Magnetization